ANALISA FISIK, BIOLOGIS DAN KIMIA TERBATAS PADA AIR SUNGAI SINGOLOT DAN AIR BERSIH YANG DIGUNAKAN OLEH PARA SANTRI SERTA KELUHAN KESEHATAN KULIT PADA PONDOK PESANTREN PURBA BARU KABUPATEN MANDAILING NATAL TAHUN 2012 - Rizki Aminah; evi Naria; Irnawati Marsaulina (Lingkungan dan Kesehatan Kerja, 2013)
Physical, biological and chemical restrictive analysis of Singolot river water and pure water that used by male students and skin health complaints in boarding school of Purba Baru, sub-distrief of Mandailing Natal on 2012. The Singolot river respresents the flow of upper stream river with hot water of Sorik Marapi. The Singolot river is one of the water that used by male students for daily necessities. The uses of this water as predicted to lead complaints of skin health in male student at the boarding school of Purba Baru. The purpose of this study was to determine physical, biological and chemical restrictive analysis of Singolot river water and pure water that used by male students and skin health complaints in boarding school of Purba Baru, sub-distrief of Mandailing Natal on 2012. The type of this study is a destcriptive survey, examined to determine the water quality and skin health complaints who had used Singolot river and pure water in boarding school of Purba Baru. The sample in this study is 98 respondents. The collecting method used by primary data, that results of the quality and the results of the questionnaire. The results showed that the water quality of the Singolot river, which do not quality are on pH (4,1) and total coliform 170/100 ml sample of water. Quality of Sisida water that flowed into the shower mosque which do not quality of turbidity that 25 FAU, color that 58,8 TCU and total coliform of water sample that 350/100 ml sample of water. Whereas Sisida river water quality supplied to all girls dormitory bathrooms is eligible water. The number of respondents who experienced by skin health complaint that 47 (48,0%) respondents. The based on the results of the study, it can be concluded that there are some parameters that do not correspondents of PP No.82 on 2001 and PERMENKES No.416/MENKES/PER/IX/1990. It is suggested tomanagement of Mustafawiyah boarding schools to manage and provide water supply facilities exspecially for the male students at the boarding school of Purba Baru. Keywords : Water Quality, Skin Health Complaint